Transitioning to smart sustainable tourist accommodation: Service innovation results. (10th November 2018) - Warren, Christopher; Becken, Susanne; Nguyen, Khoi; Stewart, Rodney A.
Abstract: This research experiment is the first study to provide detailed insights into resource use by guests staying in self-contained B&B style accommodation. Self-contained accommodation is a neglected yet important sub-industry in the hospitality sector, as it represents the largest and fastest growing share of accommodation providers in many regions. The study provides valuable data from a smart metering system, collecting data every minute over four seasons and indicates sustainable consumption opportunities using renewable energy, guest behaviour change and eco-conservation. Our results reveal that guests, when exposed to sustainability advice and communication (i.e. Intervention Group), saved 27% electricity, 22% gas, 22% water and 10% firewood. Differences between Intervention and Control Groups were also observed in terms of daily peak consumption and seasonal patterns. There are further saving opportunities, but findings also highlight social practice complexities to navigate guests' individual thermal comfort knowledge and daily routines. Transitions can be achieved through advanced smart services for direct and indirect customer feedback and host training. This paper is the first to detail findings from smart meter monitoring using high resolution at tourist accommodation, providing new insights into social practices and analysis of water energy nexus.